Autoimmune Diseases: Genes, Inflammation And Environment - Chabchoub Ghazi (International Journal of Inflammation Research, 2018)
A concise review of autoimmune disease etiology emphasizes genetic susceptibility, inflammatory pathways, and environmental exposures. It points to systems approaches for risk stratification and prevention with illustrative examples.